2019
DOI: 10.1007/s13224-019-01234-2
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter, Randomized, Open-Label Trial Comparing the Efficacy and Safety of Monoclonal Anti-Rh (D) Immunoglobulin with Polyclonal Anti-Rh (D) Immunoglobulin for the Prevention of Maternal Rh-Isoimmunization

Abstract: Objectives To compare the efficacy and safety of monoclonal anti-Rhesus (anti-D) immunoglobulin (IgG) with polyclonal anti-D IgG in the prevention of maternal Rh-isoimmunization. Methods This was a randomized, multicenter, open-label, comparative clinical trial conducted in the obstetric in-patient departments of nine tertiary care hospitals in India. 206 Rhesus (D)-negative women, not sensitized to Rh antigen, and delivering Rh positive babies, received postpartum intramuscular administration of monoclonal or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Additionally, there was discordance between RhD + RBC clearance and immunoprophylaxis among the anti-D monoclonal antibodies evaluated ( 8 ), challenging the explanation that anti-D works by clearing RhD + RBCs. Recently, two new monoclonal anti-D antibodies demonstrated efficacy in preventing RhD alloimmunization in pregnant women ( 10 , 11 ), although additional studies with a larger number of participants and re-exposure to RhD+ RBCs are required to fully evaluate the efficacy of these new therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there was discordance between RhD + RBC clearance and immunoprophylaxis among the anti-D monoclonal antibodies evaluated ( 8 ), challenging the explanation that anti-D works by clearing RhD + RBCs. Recently, two new monoclonal anti-D antibodies demonstrated efficacy in preventing RhD alloimmunization in pregnant women ( 10 , 11 ), although additional studies with a larger number of participants and re-exposure to RhD+ RBCs are required to fully evaluate the efficacy of these new therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, under certain circumstances, anti-D results in enhancement, rather than suppression, of alloimmunization to RhD (3). Finally, attempts to generate a monoclonal anti-D have largely failed, resulting in either decreased efficacy compared to donor derived anti-D, or in some cases, monoclonal anti-D has shown the same paradoxical enhancement of alloimmunization seen with certain preparations of donor derived anti-D (4,5); although a recent report indicates great progress in this area (6). Why anti-D suppresses alloimmunization in some cases and enhances alloimmunization in others remains an unsolved question.…”
Section: Introductionmentioning
confidence: 99%
“…Varying efficacies have been reported across products concerning the clearance rate of Rhpositive RBCs from blood circulation. [22][23][24][25] Chauhan et al 15 reported similarities between Rhoclone ® , a monoclonal anti-D antibody product (Bharat Serums and Vaccines Ltd., India), and its poly-anti-D counterpart with reference to clinical effects in a large number of women requiring anti-D in the clinical setting. It is noteworthy that in all studies, the safety profiles for both mono-and R-anti-D immunoglobulins have been consistent and comparable with that of poly-anti-D. 14,26 AntiD is a recombinant anti-D product that has been approved for use as an anti-D prophylaxis treatment in Rh-negative women carrying an Rh-positive fetus and who had experienced a sensitizing event during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…14 Monoclonal anti-D immunoglobulins (mono-anti-D), manufactured using the hybridoma technique, were introduced to mitigate these problems. 11,13,15 However, the maintenance of hybridoma cultures and the generation of monoclonal antibodies is a time-consuming and laborious process. Moreover, the limited availability of hybridoma growth supplements such as fetal bovine serum is a major obstacle to the adequate production of monoanti-D. 16,17 The development of recombination anti-D immunoglobulins (R-anti-D) has provided a viable option to overcome the obstacles associated with mono-anti-D.…”
Section: Introductionmentioning
confidence: 99%